CLIPPERS the brain biter: An adolescent’s experience of a rare CNS disorder - Anuar, Muhamad Azamin; Abu Bakar, Asrar; Hasan, Taufiq Hidayat; Mohamed, Mossad Abdelhak Shaban (2019)
Introduction: CLIPPERS (Chronic Lymphocytic Inflammation with Pontine Perivascular Enhancement Responsive to Steroids) is a rare inflammatory Central Nervous System (CNS) disorder prominently affecting the brainstem. We present an adolescent’s reflection on this condition further complicated with Epstein-Barr virus (EBV) induced CNS Lymphoma.